Clinical Outcomes of Patients With Primary Membranous Nephropathy and Subnephrotic Proteinuria - He, Peng; Zha, Yang; Liu, Jing; Wang, Hanmin; He, Lijie (Frontiers in Medicine, 2021)
Objectives: To update the information about the prognosis of patients with primary membranous nephropathy (MN) and subnephrotic proteinuria, and identify the relevant predictors. Methods: Four hundred and seventy-four cases of biopsy-proven primary MN with at least 18 months of follow-up were reviewed to determine the outcomes of the subgroup of patients that presented with subnephrotic proteinuria. Clinical data included initial proteinuria and microhematuria, defined as the average proteinuria/microhematuria of the first six months during the course. Outcomes included partial remission (PR), complete remission (CR), nephrotic proteinuria progression, and kidney function progression, defined as ≥ 50% loss of kidney function or end-stage kidney disease. Results: Two hundred and five patients with primary MN and subnephrotic proteinuria at biopsy were eligible. During a median follow-up of 43 months, 200 (97.56%), 167 (81.46%), and 53 (25.85%) patients attained PR, CR, and nephrotic proteinuria progression, respectively. Only one patient (0.49%) progressed to the kidney function progression. By multivariate Cox hazards regression analyses, the initial proteinuria was identified as the independent predictor for PR, CR, and nephrotic proteinuria progression with adjusted hazard ratios (aHRs) of 0.67 (95% confidence interval, 0.56-0.80), 0.50 (95% CI, 0.40-0.63), and 2.97 (95% CI, 2.23-3.97), respectively. A higher level of initial microhematuria was also associated with an increased risk of nephrotic proteinuria progression. The corresponding aHR was 1.11 (95% CI, 1.05-1.17). Conclusions: Among patients with primary MN and subnephrotic proteinuria, although the overall prognosis is excellent, dynamic detection and effective management of proteinuria remain important. In addition, initial microhematuria may be another predictor of nephrotic proteinuria progression.